Have Have We Finally Found The Happy ECE Student? A Quantitative Study Perspective : Iwan Hermawan, Gita Hindrawati, Inayah Inayah, Sartono Sartono, Danendra Rafi - Rafi Harnoko (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The learning process for children is essential to achieve cognitive and affective aspects by presenting educational learning that combines education and entertainment. Edutainment can be built through positive aspects that can be created through technology. Although several studies say that the role of technology used in the learning process produces negative results, this research aims to examine the role of technology in supporting edutainment learning. This type of study uses a quantitative approach with a sample of 163 early childhood teachers in Indonesia. Data was analyzed using SMART-PLS to evaluate the role of technology in the learning process. This test uses instrument analysis using Chi Square. Data were analyzed using SMART-PLS with validity testing using convergent and discriminant validity tests, while reliability was assessed through composite reliability and Cronbach's alpha to ensure that the instrument could be measured accurately. The findings show that the role of technology cannot stand alone in providing significance for creating an educational learning process. Educational learning can be presented with skills and competencies for teachers in navigating the teaching and learning process.